Migration and remittances in Tajikistan: Survey technical report - Alexander M. Danzer; Barbara Dietz; Kseniia Gatskova (Institut für Ost- und Südosteuropaforschung (IOS), 2013)
This paper presents the research design and data description of a household survey conducted in Tajikistan in 2011, the Tajikistan Household Panel Survey (THPS). Based on a sample of the 2007 and 2009 Tajikistan Living Standards Measurement Survey (TLSS) administered by the World Bank and UNICEF, 1,503 household were re-interviewed. The main part of the paper explains the technique of the household survey including sampling strategy, questionnaire design, pretest and fieldwork, training of interviewers and supervisors and survey quality control procedures. A short overview over the characteristics of households and respondents follows.
urn:nbn:de:101:1-201303128505
Keywords: C83; 330; Tajikistan; panel data; survey design; migration